Computational strategies for impedance boundary condition integral equations in frequency and time domains - Dély, Alexandre (2019)
The Electric Field Integral Equation (EFIE) is widely used to solve wave scattering problems in electromagnetics using the Boundary Element Method (BEM). In the frequency domain, the linear systems stemming from the BEM suffer, amongst others, from two ill-conditioning problems: the low frequency breakdown and the dense mesh breakdown. Consequently, the iterative solvers require more iterations to converge to the solution, or they do not converge at all in the worst cases. These breakdowns are also present in the time domain, in addition to the DC instability which causes the solution to be completely wrong in the late time steps of the simulations. The time discretization is achieved using a convolution quadrature based on Implicit Runge-Kutta (IRK) methods, which yields a system that is solved by Marching-On-in-Time (MOT). In this thesis, several integral equations formulations, involving Impedance Boundary Conditions (IBC) for most of them, are derived and subsequently preconditioned. In a first part dedicated to the frequency domain, the IBC-EFIE is stabilized for the low frequency and dense meshes by leveraging the quasi-Helmholtz projectors and a Calderón-like preconditioning. Then, a new IBC is introduced to enable the development of a multiplicative preconditioner for the new IBC-EFIE. In the second part on the time domain, the EFIE is regularized for the Perfect Electric Conductor (PEC) case, to make it stable in the large time step regime and immune to the DC instability. Finally, the solution of the time domain IBC-EFIE is investigated by developing an efficient solution scheme and by stabilizing the equation for large time steps and dense meshes.